Analysis of T4SS-induced signaling by H. pylori using quantitative phosphoproteomics - Glowinski, Frithjof; Holland, Carsten; Thiede, Bernd; Jungblut, Peter R.; Meyer, Thomas F. (Frontiers in Microbiology, 2014)
Helicobacter pylori is a Gram-negative bacterial pathogen colonizing the human stomach. Infection with H. pylori causes chronic inflammation of the gastric mucosa and may lead to peptic ulceration and/or gastric cancer. A major virulence determinant of H. pylori is the type IV secretion system (T4SS), which is used to inject the virulence factor CagA into the host cell, triggering a wide range of cellular signaling events. Here, we used a phosphoproteomic approach to investigate tyrosine signaling in response to host-pathogen interaction, using stable isotope labeling in cell culture (SILAC) of AGS cells to obtain a differential picture between multiple infection conditions. Cells were infected with wild type H. pylori P12, a P12ΔCagA deletion mutant, and a P12ΔT4SS deletion mutant to compare signaling changes over time and in the absence of CagA or the T4SS. Tryptic peptides were enriched for tyrosine (Tyr) phosphopeptides and analysed by nano-LC-Orbitrap MS. In total, 58 different phosphosites were found to be regulated following infection. The majority of phosphosites identified were kinases of the MAPK familiy. CagA and the T4SS were found to be key regulators of Tyr phosphosites. Our findings indicate that CagA primarily induces activation of ERK1 and integrin linked factors, whereas the T4SS primarily modulates JNK and p38 activation.